2014
DOI: 10.1111/eos.12153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non‐thermal atmospheric pressure pulsed plasma on the adhesion and durability of resin composite to dentin

Abstract: This study investigated the effect of low-power, non-thermal atmospheric pressure plasma (NT-APP) treatments, in pulsed and conventional modes, on the adhesion of resin composite to dentin and on the durability of the bond between resin composite and dentin. A pencil-type NT-APP jet was applied in pulsed and conventional modes to acid-etched dentin. The microtensile bond strength (MTBS) of resin composite to dentin was evaluated at 24 h and after thermocycling in one control group (no plasma) and in two experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 35 publications
(57 reference statements)
4
61
2
1
Order By: Relevance
“…Scanning electron microscope images (Fig. 4c, d) also showed that resin tags were longer and more tortuous with lateral projections (Han et al 2014;Zhang et al 2014), reflecting an enhanced penetration of resin into dentin tubules and tubule branches thanks to more hydrophilic tubule walls as a result of NTAP treatment. The results were consistent with the notion (mentioned in the Dental Surface Modification section) that NTAP could increase the hydrophilicity/wettability of dentin collagen or substrates, which caused the preferential infiltration of hydrophilic components.…”
Section: Resin Penetrationmentioning
confidence: 92%
See 2 more Smart Citations
“…Scanning electron microscope images (Fig. 4c, d) also showed that resin tags were longer and more tortuous with lateral projections (Han et al 2014;Zhang et al 2014), reflecting an enhanced penetration of resin into dentin tubules and tubule branches thanks to more hydrophilic tubule walls as a result of NTAP treatment. The results were consistent with the notion (mentioned in the Dental Surface Modification section) that NTAP could increase the hydrophilicity/wettability of dentin collagen or substrates, which caused the preferential infiltration of hydrophilic components.…”
Section: Resin Penetrationmentioning
confidence: 92%
“…With a fixed treatment time of 30 s, significantly higher µTBS was recorded on NTAP-treated dentin, and fractographic analysis revealed that NTAP-treated specimens exhibited less frequent interfacial and mixed failures (Dong et al 2013). In a recent study, Han et al (2014) used a 3-step total-etch adhesive for bonding to dentin. The NTAP treatment (30 s) followed acid etching and preceded rewetting and primer application.…”
Section: Bond Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the intraoral use of hydrofluoric acid should be omitted [4]. APP treatment might promote improved adhesion of repair material to enamel/dentin surface, due to enhance the surface energy of adhered tooth substrate [37][38][39]. In our previous and present studies, however, neither APP nor UV could improve the bond strength between a repair material (resin composite) and ceramic-based CAD/CAM indirect restorative materials [40].…”
Section: Discussionmentioning
confidence: 83%
“…The adhesive-dentin interface is the weakest link in the tooth-restoration complex 1 . The interaction between dentin and resin monomers depends on surface conditioning 2 , and optimal dentin bonding occurs when adhesive monomers infiltrate completely into the mineralized dentin fibril network after etching 3 .…”
Section: Introductionmentioning
confidence: 99%